La música infantil para desarrollar el lenguaje verbal y no verbal de las niñas y niños de 0 a 3 años del centro de educación inicial My Little Friends de la ciudad de Loja. Período 2014-2015 - Delgado Labanda, Guissella Katherine (2016)
The present research work entitled: The children's music to develop verbal and non-verbal language of children from 0-3 years of the Center for Early Education My Little Friends of the city of Loja. 2014-2015. It had as general objective to identify the importance of children's music to develop verbal and nonverbal language in children. For development was used the following methods such as: scientific, descriptive, inductive-deductive, analytical and synthetic, the techniques and instruments used were the survey apply to 6 teachers, it was an individually form and its purpose was to gather information the use and benefits of children's music in the language of infants. And for children the Language Development Instrument (Manzano Mier M., S. Correa, M. Perera 1987) it consists of 17 items divided into three categories: communication area, regulation and vocabulary, which allow a vision the level at which children are in terms of verbal and non-verbal language. The type of study is descriptive: the sample consisted of 21 girls and 23 boys for a total of 44 children and 6 teachers. The main results of the research we have 100% of teachers indicate that they use children's music the daily work as a methodology for the development of verbal and non-verbal language of children. In conclusion we have: children's music (children's songs) in the teaching-learning process is very important as it increases the class and increase vocabulary in children, just as we have to use children's music in the workday, development aid verbal and nonverbal language